PENGARUH LEARNING ORIENTATION TERHADAP INNOVATIVE BEHAVIOR PADA STUDENT UNION DI UNIVERSITAS CIPUTRA - khrisnanda Choti (Universitas Ciputra Surabaya, 2021)
The propose of this research is to find out the effect of individual innovative behavior on individual innovative behavior with work group cohesion as mediating variable in the context of virtual teams. The method that is used in this research is the analysis method in the form of Partial Least Square (PLS) with software SmartPLS. The sample in this research is the Student Union member of 2020/2021 period International Business Management major that is the number of 36 respondents. Data collection technique in this research is to distribute google form questionnaires with likert scale measurement. Based on data analysis, it is concluded that individual learning orientation (X) and individual innovative behavior (Y) are significant.